High Speed RGB-Based Duobinary-Encoded Visible Light Communication System Under the Impact of Turbulences - Li, Lin; Sharma, Abhishek (Frontiers in Physics, 2022)
The recent gain in the pervasiveness of Visible Light Communication due to its ability to simultaneously provide lighting and communication solution has projected it as the best candidate for smart city infrastructure to have seamless connectivity. The fundamental challenge of this technology is to ensure high data rate communication while meeting the lighting requirements of smart cities. This work is focused on providing high data rate capacity using visible light communication. To realize this, diffused channel modeling and - channel modeling have been considered. 6 channels each carrying 10 Gbps data are multiplexed using polarization division multiplexing and wavelength division multiplexing transmitted over a diffused channel of 1.3 meters. While the ranges of 8 meters under clear conditions and 5 meters under heavy attenuation are reported with - modeling, the reported results show successful transmission of data in terms of bit error rate and eye diagram.